Plasma Aldosterone Levels Are Not Associated With Cardiovascular Events Among Patients With High‐Risk Vascular Disease: Insights From the ACCELERATE Trial - Kumar, Anirudh; Patel, Divyang R.; Brennan, Danielle M.; Wolski, Kathy E.; Lincoff, A. Michael; Ruotolo, Giacomo; McErlean, Ellen; Weerakkody, Govinda; Riesmeyer, Jeffrey S.; Nicholls, Stephen J.; Nissen, Steven E.; Menon, Venu (Journal of the American Heart Association, 2019)
Background The failure of cholesteryl ester transfer protein inhibitor torcetrapib was associated with an off-target increase in plasma aldosterone. We sought to evaluate the impact of evacetrapib on plasma aldosterone level and determine the association between plasma aldosterone level and major adverse cardiovascular events among patients with stable high-risk vascular disease enrolled in the ACCELERATE (Assessment of Clinical Effects of Cholesteryl Ester Transfer Protein Inhibition With Evacetrapib in Patients at a High Risk for Vascular Outcomes) trial. Methods and Results We included all patients with a plasma aldosterone level (N=1624) and determined the impact of evacetrapib exposure compared with placebo on plasma aldosterone levels after 12 months of treatment. Using baseline and postexposure aldosterone levels, hazard ratios for major adverse cardiovascular events (cardiovascular death, nonfatal myocardial infarction, cerebrovascular accident, hospitalization for unstable angina, and revascularization) with increasing quartile of baseline and percentage change in plasma aldosterone level at follow-up were calculated. The average age was 65.2 years, 75.7% were men, 93.7% were hypertensive, 73.3% were diabetic, and 57.6% had a prior myocardial infarction. Baseline plasma aldosterone level (85.2 [43, 150] versus 86.8 [43, 155] pmol/L; =0.81) and follow-up percentage change (13.6% [-29, 88] versus 17.9% [-24, 87]; =0.23) were similar between those who received evacetrapib and placebo. During median follow-up of 28 months, major adverse cardiovascular events occurred in 263 patients (16.2%). The hazard ratios for increasing quartile of baseline or percentage change in plasma aldosterone level at follow-up were not significant for major adverse cardiovascular events. These findings remained consistent when adjusting for significant characteristics. Conclusions Exposure to evacetrapib did not result in significant change in plasma aldosterone levels compared with placebo. Among patients with stable high-risk vascular disease, plasma aldosterone levels were not a predictor for future cardiovascular events. Clinical Trial Registration URL: http://www.ClinicalTrials.gov. Unique identifier: NCT01687998.